Analyzing the Impact of Learning Technology on the Quality of Education in Schools: Potential and Risks - Ahmad Robith Firdausi (Journal of Pedagogi, 2024)
This research examines the impact of learning technologies on the quality of education in schools, focusing on the potential and associated risks. In the digital era, the integration of technology in the teaching and learning process is becoming increasingly important. This research method uses a qualitative approach with literature study techniques to analyze and understand the impact of learning technology on the quality of education. Learning technology contributes significantly to improving the quality of education in schools, both in terms of accessibility and quality of learning processes. Technology allows students to access a wide range of information sources and learning materials and supports more flexible and interactive learning. With educational apps, learning videos and online platforms, students can study independently outside of school hours and adapt learning to their own style and pace. This helps to create a more personalized and adaptive learning experience, which results in increased student motivation and understanding of the material. However, the application of technology in education also brings a number of risks that need to be taken seriously. One of the main risks is that students' dependence on technological devices can reduce their ability to think critically and solve problems independently. This implies that schools and governments need to develop policies that support the effective application of technology, including teacher training in integrating technology with the curriculum, provision of adequate infrastructure, and efforts to ensure equal access for all students.